Signal regulatory protein alpha initiates cachexia through muscle to adipose tissue crosstalk. Issue 6 (11th September 2019) - Wu, Jiao; Dong, Jiangling; Verzola, Daniela; Hruska, Keith; Garibotto, Giacomo; Hu, Zhaoyong; Mitch, William E.; Thomas, Sandhya S.
Abstract: Background: Muscle wasting from chronic kidney disease (CKD) or from defective insulin signalling results in morbidity and, ultimately, mortality. We have identified an endogenous mediator of insulin resistance, signal regulatory protein alpha (SIRPα), which leads to cachexia in mice and is associated with cachexia in patients with CKD. Methods: We assessed insulin signalling and mechanisms causing muscle atrophy plus white adipose tissue (WAT) metabolism in mouse models of CKD or acute diabetes (streptozotocin treatment). We then examined these factors in mice with global knockout (KO) of SIRPα and sought mediators of metabolic responses in muscle and adipose tissues of mice with either muscle‐specific or adipose tissue‐specific KO of SIRPα. Metabolic responses were confirmed in primary cultures of adipose cells. Results: In mice with CKD, SIRPα expression was increased in WAT (three‐fold, P < 0.05), and this was associated with precursors of cachexia: 'pathologic browning', thermogenesis, and a two‐fold activation of protein kinase A ( P < 0.05 vs. control mice) plus loss of adipose tissue mass. In contrast, mice with SIRPα global KO and CKD or acute diabetes experienced improved insulin signalling and activation of pAkt plus 'physiologic browning' of WAT. These mice avoided losses of muscle and adipose tissues and experienced a 31% improvement in survival ( P < 0.05) than did wild‐type mice with CKD. In muscle‐specific SIRPα KO mice with CKD, we uncovered that serum SIRPα levels ( P < 0.05) were suppressed and were associated with improved insulin signalling both in skeletal muscles and in WAT. These changes were accompanied by physiologic WAT browning. However, in adipose‐specific SIRPα KO mice with CKD, levels of serum SIRPα were increased over two‐fold ( P < 0.05), while muscle losses were minimally inhibited. Clinical implications of SIRPα signalling are suggested by our findings that include increased SIRPα expression in muscle and adipose tissues ( P < 0.05 vs. healthy controls) plus higher SIRPα levels in the serum of patients with CKD (2.4‐fold, P =0.000017 vs. healthy controls). Conclusions: Our results show that SIRPα plays an important role as an anti‐insulin mediator regulating pathways to cachexia. In muscle‐specific SIRPα KO, changes in SIRPα serum levels seem to improve insulin signalling in muscle and WAT, suggesting crosstalk between muscle and adipose tissue. Therefore, targeting SIRPα may prevent cachexia in patients with CKD or acute diabetes.